Creating the organization of the future : building on Drucker and Confucius foundations - Cheung, Virginia (Emerald Publishing Limited, 2023)
Eastern philosophy and Western management ideals offer a powerful set of wisdom on how to build and grow businesses. This can have lasting impact on employees, customers, financial performance, and society. The father of modern management - Peter F. Drucker - focused on how organizations can contribute to a functioning society. Confucius focused on how to build a functioning society, largely from a family and individual perspective. Despite these differing starting points, their collective work provides a remarkably consistent set of principles that can provide practical guidance for executives who want to both "win in the present" and create their own future. The purpose of this book is to help leaders and decision-makers successfully navigate their organizations through the stormy seas of the present, into the future. In the first section of the book, the authors demonstrate how executives can make five direction-setting 'big choices' for their firms. These five big choices are: defining the purpose of an organization, building a mission statement, setting an organization's vision, crafting organizational values, and shaping the firm's culture. In the second section, the authors tie these five choices to the foundational thinking of Drucker and Confucius. Here the concepts, principles, and real-world practice of Eastern and Western leadership are shown here to combine to compelling effect.
Keywords: Organizational change.; Business -- Philosophy.; Philosophy, Asian.; Success in business.; Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; elektronické knihy; electronic books